P32 A Novel Automated Referral System Using The Electronic Prescription Of Prednisolone ≥30 Mg And Nebulised Bronchodilators To The Respiratory Specialist Team Is Robust And Effective. (10th November 2014) - Colclough, RC; Avent, T; Breese, K; Craddock, C; Curry, D; Swindells, K; Gompertz, S
Abstract : Introduction: Patients admitted to hosptial with an exacerbation of COPD should be cared for by respiratory teams (COPD Quality Standard 10, NICE 2011). The earlier the patient is reviewed by a specialist the greater the impact on length of stay (COPD NICE guideline 101, 2010). A rigorous and rapid referral system is required. A new electronic referral system triggered by the prescription of prednisolone >=30 mg AND nebulised bronchodilators (salbutamol and/or ipratropium) via our Prescribing Information Communication System (PICS) was implimented. This replaced the laborious paper sift of the admissions book for admissions with airway exacerbations. The general medical team was also permitted to refer directly to the respiratory team via email. Referral numbers were compared over a 2-month period to ensure that the new automated system is robust. Method: The new automated referral was created. Data was collected from the three referral routes a) paper sift, b) automated referral system, c) email from general medical team. Comparison between: a) monthly automated and email referrals was made, b) paper sift and automated referrals route was made. Results: Each month there were: 262 (mean) admissions screened via paper sift of which 96 (mean) were inappropriate (36%). No patients identified by paper sift or email were missed by the automated system. 138 (mean) automated referrals- time from admission to automated referral 13 h (mean) 10–16 h (range). 75 (mean) email referrals - time from admission to email referral 104 h (mean)- 96–112 (range). Conclusion: Paper sift is time costly and laborious with a third of referrals inappropriate. Automated referrals are sent 91 (mean) hours quicker than emai referrals. Automated referrals reduce the delay between admission and specialist review. They can be received from any location in the hospital throughout the day using Smart Phones. The automated referral eliminates the need for once daily paper sifting of the admission book, and replaces it with a more timely and robust method of directing the specialist respiratory team to the patient's bedside.